2013
DOI: 10.1093/ndt/gft244
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate control in end-stage renal disease: barriers and opportunities

Abstract: Hyperphosphatemia is a nearly universal complication of end-stage renal disease that is widely recognized as one of the most important and most challenging clinical targets to meet in the care of dialysis patients. Left untreated, it can lead to bone pain, pruritus and worsening secondary hyperparathyroidism. Data from observational studies demonstrate that an elevated serum phosphorus level is an independent risk factor for mortality, and that treatment with phosphate binders is independently associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 56 publications
(68 reference statements)
0
66
1
4
Order By: Relevance
“…Regarding the total mass of phosphate removed, nocturnal HD is the superior method compared to conventional HD and peritoneal dialysis . Our results showed a much higher total phosphate reduction per session compared to reductions between 600 and 1200 mg per session found in the literature . However, these results are from a study conducted by Musci et al in 1994/95 .…”
Section: Discussioncontrasting
confidence: 65%
“…Regarding the total mass of phosphate removed, nocturnal HD is the superior method compared to conventional HD and peritoneal dialysis . Our results showed a much higher total phosphate reduction per session compared to reductions between 600 and 1200 mg per session found in the literature . However, these results are from a study conducted by Musci et al in 1994/95 .…”
Section: Discussioncontrasting
confidence: 65%
“…Hyperphosphataemia causes pruritus, renal osteodystrophy, hyperparathyroidism and calcification of the heart and blood vessels and increases mortality. Statistics showed that mortality increases when SPVs are higher than 5Á5 mg/dl (Kestenbaum et al 2005, Spasovski 2007, Waheed et al 2013.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the mechanism underlying uraemic pruritus (UP) is poorly understood, multiple factors have been proposed as pruritogenic substrates, among which vitamin A, parathyroid hormone, histamine, and calcium and magnesium salts may induce itching (Narita et al 2008, Mettang & Kremer 2015. Furthermore, hyperphosphataemia and secondary hyperparathyroidism have been related to pruritus (Chou et al 2000, Virga et al 2002, Waheed et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…An elevated serum inorganic phosphate (Pi) level is an independent risk factor for mortality, and treatment with Pi binders is independently associated with improved survival in chronic kidney disease (CKD) patients [1,2]. Findings from experimental studies support the epidemiologic findings: clinical practice guidelines recommend specific targets for serum Pi levels in dialysis patients [3][4][5].…”
Section: Introductionmentioning
confidence: 97%